Importance of Task Selection for Connected Speech Analysis in Patients with Alzheimer's Disease from an Ethnically Diverse Sample. - Bose, Arpita; Dutta, Manaswita; Dash, Niladri S.; Nandi, Ranita; Dutt, Aparna; Ahmed, Samrah (Journal of Alzheimer's Disease, 2022)
Features of linguistic impairment in Alzheimer's disease (AD) are primarily derived from English-speaking patients. Little is known regarding such deficits in linguistically diverse speakers with AD. We aimed to detail linguistic profiles (speech rate, dysfluencies, syntactic, lexical, morphological, semantics) from two connected speech tasks-Frog Story and picture description-in Bengali-speaking AD patients. The Frog Story detected group differences on all six linguistic levels, compared to only three with picture description. Critically, Frog Story captured the language-specific differences between the groups. Careful consideration should be given to the choice of connected speech tasks for dementia diagnosis in linguistically diverse populations.